Usage and Influence of Dietary Supplementation Amongst Adolescent Athletes - Allison Harlow; Jennifer Walker; Aubrey Wagstaff (Bowling Green State University, 2023)
The purpose of this study was to investigate the use of dietary supplements or ergogenic aids amongst high school athletes.